2011
DOI: 10.1002/jcla.20469
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia‐modified albumin as a biochemical marker in children with neuroblastoma and soft tissue sarcomas

Abstract: In this study, the levels of ischemia-modified albumin (IMA) in pediatric oncology patients with soft tissue sarcomas (STSs) and neuroblastoma (NB) were analyzed. To date, there have been no studies concerning IMA in these groups of patients. Ninety-nine children with STSs and NB were analyzed from 2006 to 2009, and 30 healthy children were also enrolled in the study. IMA levels were measured throughout treatment in all patients. The levels of IMA in all cancer patients (mean 116.8±39.3 U/ml), in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Also, in this study there was no comparision for serum albumin levels of patients and control group. Stachowicz-Stencel et al (2011) found that serum IMA levels were statistically higher in pediatric patients with neuroblastoma and soft tissue sarcomas. They reported a weak negative correlation between serum IMA and albumin levels in participiants.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, in this study there was no comparision for serum albumin levels of patients and control group. Stachowicz-Stencel et al (2011) found that serum IMA levels were statistically higher in pediatric patients with neuroblastoma and soft tissue sarcomas. They reported a weak negative correlation between serum IMA and albumin levels in participiants.…”
Section: Discussionmentioning
confidence: 88%
“…Also, serum IMA levels increased in patients with gastric, prostate, soft tissue cancer and neuroblastoma (Mastella et al, 2009;Stachowicz-Stencel et al, 2011;Fidan et al, 2012). There is no published report about serum concentrations of IMA in patients with BC.…”
Section: Introductionmentioning
confidence: 99%
“…Patients did not have manifestations of acute infection and or liver and kidney failures. Stencel et al, in a study they conducted with pediatric cancer patients, evaluated IMA levels and found them to be higher in the patient group compared to the controls (16). In another study conducted with patients with prostate disease and myocardial infarction, IMA was detected to be high in those with prostate hyperplasia and myocardial ischemia, while no difference was observed in prostate cancer patients (17).…”
Section: Discussionmentioning
confidence: 98%
“…İMA gastrik, prostat, yumuşak doku kanserleri ve nöroblastomlarda artmıştır. Fidan ve arkadaş-larının mide kanserli hastalarda, Stachowicz-Stencel ve arkadaşlarının nöroblastoma ve sarkomalı çocuklarda, Ellidag ve arkadaşlarının mesane kanserli ve kolorektal kanserli hastalarda yaptıkları çalışmalarında İMA'nın artmış olduğu gösteril-di (10,(45)(46)(47) .…”
Section: Kalp Dişi İskemi̇k Hastaliklarunclassified